Characteristics of Edible Film from Corn Starch (Zea mays L.) with Additional Glycerol and Variations of Zinc Oxide (ZnO) Nanoparticles - Ifmalinda Ifmalinda; Siti Azzahra Kurnia; Dinah Cherie (Green Engineering Society, 2023)
Plastic is one of the most widely used packaging materials. Plastic is made of chemicals that are highly toxic, and its use has produced a lot of waste that is bad for the environment and difficult to decompose. The global community is becoming more and more aware of the value of high-quality food, particularly when it comes to packaging that is safe for human health and the environment. Edible films can be used as an eco-friendly alternative to plastic food packaging options. As a material for packaging, edible film made of biopolymers has been created. This material can be made from biodegradable components and has qualities akin to those of ordinary plastics. When combined with zinc oxide (ZnO), a piezoelectric ceramic with anti-microbial properties, edible film degrades and decomposes readily. This study sets out to identify the effects of variations in zinc oxide nanoparticle concentration properties of edible films made from corn starch (Zea mays L.) and to establish the optimal zinc oxide nanoparticle concentration. ZnO concentrations ranging from 0% to 3% to 9% to 12% were used. The outcomes demonstrated that a concentration of 12% provided the optimal treatment for the properties of edible film. With the addition of 12% ZnO concentration, the edible film's properties improved the most in this investigation, showing 81.94% water resistance, 1.434 MPa tensile strength, and 38.46% elongation percent. The lowest biodegradability value was found in edible film with a concentration of ZnO 12%, within 14 days. The resistivity, tensile strength, and % elongation of the edible film increase with increasing ZnO content.